BIOMETRIC AND POST-HARVEST VARIABLES OF HYDROPONIC LETTUCE TREATED WITH LOW-FREQUENCY ELECTRICAL PULSES - Tellez, Hayver Olaya [UNESP]; Capuani, Silvia [UNESP]; Jacon, Camila Paula Rossetto Pescatori [UNESP]; Putti, Fernando Ferrari [UNESP]; Villas Bôas, Roberto Lyra [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2023)
Leafy vegetables are commercially important because of the implementation of technologies that increase their productivity. Products that can be consumed fresh to gain commercial importance. Production techniques such as hydroponic methods generate good results but can still be refined. Reports indicate that the treatment of irrigation water with low-frequency electrical pulses can increase the productivity of crops, increasing the demand for the development of detailed studies. In this sense, the objective of the present work was to analyze the development of biometric and postharvest variables of hydroponic lettuce with nutrient solution treated with low-frequency electrical pulses. An entirely randomized design with a factorial scheme was used, with 3 × 2 × 3 subsubdivid installments and four repetitions. The factors were the frequency of application of electrical pulses (constant, intermittent and unused), two concentrations of nutrient solution and three production cycles. The development and postharvest performance of lettuce subjected to low-frequency electrical pulses, regardless of the nutrient mixture, were similar to those of untreated plants, indicating a low influence on development technology.
VARIÁVEIS BIOMÉTRICAS E PÓS-COLHEITA DA ALFACE HIDROPÔNICA TRATADA COM PULSOS ELÉTRICOS DE BAIXA FREQUÊNCIA
Keywords: Chlorophyll; innovation; mass loss; technology